2021
DOI: 10.3390/ijms22126550
|View full text |Cite
|
Sign up to set email alerts
|

Role of Anesthetics and Their Adjuvants in Neurovascular Protection in Secondary Brain Injury after Aneurysmal Subarachnoid Hemorrhage

Abstract: Aneurysmal rupture accounts for the majority of subarachnoid hemorrhage and is responsible for most cerebrovascular deaths with high mortality and morbidity. Initial hemorrhage severity and secondary brain injury due to early brain injury and delayed cerebral ischemia are the major determinants of outcomes after aneurysmal subarachnoid hemorrhage. Several therapies have been explored to prevent these secondary brain injury processes after aneurysmal subarachnoid hemorrhage with limited clinical success. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Midazolam, propofol and dexmedetomidine are the most used sedatives [ 6 , 8 , 9 ]. Previous studies have demonstrated that sedatives might play roles in altering the outcome of the brain-injured patients; however, the influences of different agents are divergent [ 10 ]. Low dose dexmedetomidine, rather than no use, is significantly associated with higher rate of favorable outcome in poor-grade SAH patients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Midazolam, propofol and dexmedetomidine are the most used sedatives [ 6 , 8 , 9 ]. Previous studies have demonstrated that sedatives might play roles in altering the outcome of the brain-injured patients; however, the influences of different agents are divergent [ 10 ]. Low dose dexmedetomidine, rather than no use, is significantly associated with higher rate of favorable outcome in poor-grade SAH patients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that sedatives might play roles in altering the outcome of the brain-injured patients; however, the influences of different agents are divergent [ 10 ]. Low dose dexmedetomidine, rather than no use, is significantly associated with higher rate of favorable outcome in poor-grade SAH patients [ 10 , 11 ]. Dexmedetomidine also exerts brain protective effect in patients with intracranial aneurysm [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations